Heads up Descemet membrane endothelial keratoplasty performed using a 3D visualization system. Issue 11 (28th November 2017) - Galvis, Virgilio; Berrospi, Ruben D; Arias, Juan D; Tello, Alejandro; Bernal, Julio C
Abstract: A 68-year-old female underwent Descemet membrane endothelial keratoplasty (DMEK) in her right eye using a 3D visualization system with the surgeon looking directly to a digital screen instead of through the eyepieces of the surgical microscope. The procedure was uneventful. Five weeks after the surgery the DMEK graft was in good position and totally adhered, the cornea clear and uncorrected distance visual acuity 20/50. This is the first reported case of DMEK using 3D augmented reality visualization system. It seems to offer advantages for the corneal surgeon in critical steps of the endothelial grafting procedure.